Determination of ketoacids in drinking water by DNPH derivatization and LC-ESI-MS/MS1. Issue 15 (7th August 2015) - Mao, Yu-qin; Wang, Xiao-mao; Tang, Shun; Yang, Hong-wei; Xie, Yuefeng F.
<x xml:space="preserve">Abstract</x> A quantitative method for determination of ketoacids, including glyoxylic acid, pyruvic acid and ketomalonic acid, in ozonated drinking water was developed by using 2, 4-dinitrophenylhydrazine (DNPH) derivatization combined with liquid chromatography-electrospray mass spectrometry analysis.